Routes to Reading and Spelling: Testing the Predictions of Dual‐Route Theory. Issue 4 (26th March 2016) - Sheriston, Lee; Critten, Sarah; Jones, Emily
Abstract: Dual‐route theory, which emphasizes the importance of lexical and nonlexical routes, makes specific predictions about the kinds of strategies that young students might adopt when attempting to correctly read and spell regular and irregular words. The current study tests these predictions by assessing strategy choice on regular, irregular, and nonword items among a group of 55 English‐speaking students ages 8–10 years. Performance measures and verbal self‐reports were used to classify strategy choice in reading and spelling. The results confirmed that students were able to draw from a wide repertoire of coexisting strategies to support their reading and spelling activities. Hierarchical regression analyses revealed that pure lexical retrieval could best predict reading and spelling accuracy scores on irregular words, whereas both lexical and nonlexical strategies could, to varying degrees, predict scores on the regular items. Unexpectedly, none of the reported reading or spelling strategies could accurately predict students' scores on the nonword items after controlling for age. The theoretical implications for the application of dual‐route theory to early reading and spelling, especially in relation to nonword performance, are discussed and outlined.